A Methods engineering study on Yoshida Kogyo Kabushiki (YKK), Inc. - Ambida, Julie-Ann; Baluyot, Danica; Magtibay, Rhea Joy; Malabuyoc, Anabelle (College of Engineering, 2004)
Yoshida Kogyo Kabushiki Inc. is a fabricating company that manufactures zippers. It produces 3 types of zippers : vision, metal and plastic fastener zippers. 80 percent of its production is for exportation and 20 percent are generated for local use. Their major customers are Levi's, Samsonite, Jansport, Jag, Bench and many other more leading brands of clothing line and bags. This study is focused on methods improvement since the company aims for higher worker efficiency, which in turn increases the production, thus, satisfy the customers and maintain the quality they are known for. Methods documentation and analysis is done on actual plant visits, employing various tools learned in the Methods Engineering class. The study centered on the following problems : Unsystematic factory layout, Worker inconveniences/Lack of drinking fountain and comfort rooms, Wrong layout (warehouse), Poor housekeeping and maintenance, Lack of training and briefing for the workers, and delay of imported materials/large number of idle machines. The group's job is to generate probable solutions to the problems stated above. The members of the group generated at least one alternative for each problem. A certain criterion was established and is used to evaluate each alternative. And in turn, each alternative was reviewed regarding the risks that could affect the present system. The alternatives that are further chosen are those that are the most efficient. The selected alternatives are subjects for implementation. The group is required to come up with an implementation plan and strategy that will serve as guide for the chosen company so that they may be able to apply the challenges by the alternatives. After thorough analysis of the problems and various solutions generated by the group, each predicament was given an elucidation. For the unsystematic factory layout, the alternative where the pathways are rearranged and all departments are occupied was chosen. New location of water dispenser and lowering of temperature in the dyeing area is the solution for the worker inconvenience/lack of drinking fountains and comfort rooms. For the third problem identified, wrong warehouse layout, the practical solution is the construction of a guardhouse outside the office where the supervising attendant will be stationed and safety equipment will be kept. Furthermore, general housekeeping in the warehouse and installation of accessible fire extinguishers were addressed. For poor housekeeping (manufacturing plant) problem, the solution is to replace fluorescent lights and repair roof leaks. To conduct first hour meetings is the chosen alternative solution for the lack of training and briefing of workers. For the last problem, delay of imported goods/large number of idle machines, it is most efficient to stop the importation and bring back the textile production. All of the solutions preferred by the group were carefully studied and weighed based on the criteria set for the assurance of efficient and effective outcomes.